(untitled) (Medico Legal Update, 2020)
Providing a stimulus given shortly after the baby is born gives a very important effect for the development of children. In the development of a child, stimulation is a basic need and also plays an important role to develop. Dewanti,1 revealed that baby spa is one form of nonverbal communication that can be done by the mother. This spa treatment is very beneficial for baby’s health and development. Infants who have been treated with the spa will look fresh, healthy, vibrant and growth and development faster than infants who never did at all spa. In addition to the baby spa, music therapy is also one therapy that can stimulate thinking, improve concentration and memory, and can improve the cognitive development of infants and children. Music therapy is an effort to improve physical and mental quality with sound stimuli consisting of melodies, rhythms, harmony, timbre, shapes and styles that are organized in such a way as to create useful music for mental and mental health2. This study was conducted to determine the development of infants through baby spa and music therapy, and useful as a follow-up to improve the growth and development of the baby so that the maximum. The population in this study is 6-12 months old baby with sampling using quota sampling technique with a sample of 60 babies. Quantitative quasi-experimental research method with the only posttest with control group design approach, where in the case group was given continuous intervention for 16 days while in the control group only 1 interval was given at the beginning of the meeting, at the end of the study the two groups will be measured the level and compared the results, with the General Linear Model Repeated Measures (GLM RM) test. The result showed that the average of the first measurement scores in the lower case group was slightly lower than the control group that was 8.97 (SD = 0.928), while the mean score on the second measurement and the third measurement in the case group was higher than the control group 9.53 (SD = 0.776) and 9.80 (SD = 0.484). The result of the analysis with multivariate approach showed significant difference KPSP score for growth and development on the third level of measurement (p-value <0,007). Multivariate analysis can explain the variation of growth and development variable amount of 16,1%, there was a significant effect difference between case group and control group in improving growth and development score (p-value <0.000) amount of 44.7%.